2020
DOI: 10.3892/etm.2020.9364
|View full text |Cite
|
Sign up to set email alerts
|

Research and prospect of peptides for use in obesity treatment (Review)

Abstract: Obesity and its related diseases, such as type 2 diabetes, hypertension and cardiovascular disease, are steadily increasing worldwide. Over the past few decades, numerous studies have focused on the differentiation and function of brown and beige fat, providing evidence for their therapeutic potential in treating obesity. However, no specific novel drug has been developed to treat obesity in this way. Peptides are a class of chemically active substances, which are linked together by amino acids using peptide b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 147 publications
(183 reference statements)
0
7
0
Order By: Relevance
“…The third is due to therapeutic successes in diseases such diabetes and obesity, which require larger production volumes of drugs (>100 kg). 16 During the last six years (2015–2021) several research groups from academia and industry devoted incredible efforts to improve efficacy and greenness of peptide production, as witnessed by the large number of publications and patents on the topic. The bloom of new approaches to upstream and downstream technologies is fragmented.…”
Section: Introductionmentioning
confidence: 99%
“…The third is due to therapeutic successes in diseases such diabetes and obesity, which require larger production volumes of drugs (>100 kg). 16 During the last six years (2015–2021) several research groups from academia and industry devoted incredible efforts to improve efficacy and greenness of peptide production, as witnessed by the large number of publications and patents on the topic. The bloom of new approaches to upstream and downstream technologies is fragmented.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study demonstrated that no obvious clinical symptoms of poisoning, such as diarrhea, abdominal pain, or even death, were observed in growing pigs after ingesting FB 1 but th pigs' food intake and weight gain were significantly reduced. Studies suggested that abnormal secretion and unbalanced regulation of brain-gut peptides are one of the main reasons for food intake and energy metabolism [31]. According to their different effects on appetite regulation, brain-gut peptides can be divided into two categories, namely appetite-promoting (including NPY, ghrelin, etc.)…”
Section: Appetite-related Brain-gut Peptidementioning
confidence: 99%
“…The importance of circulating miRNAs for obesity is still remain unclear, while research is trying to expose the connections between miRNAs and obesity. In terms of obesity, multiple researchers have described different miRNA expression profiles, and these findings are discussed in the literature [22,24,25]. Many research concentrate on model systems, so there is a lack of human subject knowledge.…”
Section: Micrornas and Obesitymentioning
confidence: 99%